2023
DOI: 10.2196/35917
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the Quality Management of Patient-Generated Health Data in Remote Patient Monitoring: Mixed Methods Study

Abstract: Background Patient-generated health data (PGHD) collected from innovative wearables are enabling health care to shift to outside clinical settings through remote patient monitoring (RPM) initiatives. However, PGHD are collected continuously under the patient’s responsibility in rapidly changing circumstances during the patient’s daily life. This poses risks to the quality of PGHD and, in turn, reduces their trustworthiness and fitness for use in clinical practice. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Recent research has revealed that personalized healthcare is increasingly prevalent [75,76]. Therefore, it is crucial to re-evaluate management procedures for processing patient-generated data of a high quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has revealed that personalized healthcare is increasingly prevalent [75,76]. Therefore, it is crucial to re-evaluate management procedures for processing patient-generated data of a high quality.…”
Section: Discussionmentioning
confidence: 99%
“…The themes of HISs and technology adoption frequently centers on the effective management strategies and adoption of novel technologies. Recent studies highlight the rapid acceleration of technology adoption, necessitating the revision of management strategies [75,76]. Previous themes may relate to broader work on technology adoption.…”
Section: Evaluation In Terms Of Co-citation Analysismentioning
confidence: 99%
“…This poses risks to the quality of PGHD and, in turn, reduces their trustworthiness and fitness for use in clinical practice. Recently a guideline was developed describing a systemic approach to data quality management of PGHD so that these data can be reliably used in clinical care ( 74 ). In the future, special attention should be given to the cost-effectiveness of such models and their sustainability.…”
Section: Discussion: Challenges and Limitations Of The Proposed Metho...mentioning
confidence: 99%
“…The adoption of mobile apps and wearable devices with sensor technologies has rapidly increased in the healthcare field. 1 , 2 Health apps provide patients with a streamlined means of collecting their health data outside the clinical environment and enable the collection of large amounts of person-generated health data (PGHD) through the activities of daily living. 3 , 4 As reported by Research2Guidance, more than 259,000 mobile health apps are available in online app stores.…”
Section: Introductionmentioning
confidence: 99%